The study of the daily dynamics of the cardio-vascular system in adolescents in the fall spring of the year (Eurasian Journal of Ecology, 2016)
The features of daily dynamics of the cardio-vascular system in adolescents were set in the fall spring of the year for the first time. The features of the parameters of the daily dynamics of heart rate (HR) and the parameters of heart rate variability (HRV) in adolescents (and male and female) were shown in the fall spring of the year.
Keywords: А daily dynamics; the cardiovascular system; adolescents; spring; electrocardiography (ECG); circadian rhythm; ventricular extrasystoles (VES); heart rate (HR); heart rate variability (HRV).